Joint cationic and anionic redox chemistry in a vanadium oxide cathode for zinc batteries achieving high energy density - Wenfeng Wang; Lu Zhang; Zeang Duan; Ruyue Li; Jiajin Zhao; Longteng Tang; Yiming Sui; Yadi Qi; Shumin Han; Chong Fang; Desong Wang; Xiulei Ji (Carbon Energy)
Abstract Rechargeable aqueous zinc batteries are promising for large‐scale energy storage due to their low cost and high safety; however, their energy density has reached the ceiling based on conventional cathodes with a single cationic redox reaction mechanism. Herein, a highly reversible cathode of typical layered vanadium oxide is reported, which operates on both the cationic redox couple of V5+/V3+ accompanied by the Zn2+ storage and the anionic O–/O2– redox couple by anion hosting in an aqueous deep eutectic solvent electrolyte. The reversible oxygen redox delivers an additional capacity of ∼100 mAh g–1 at an operating voltage of ∼1.80 V, which increases the energy density of the cathode by ∼36%, endowing the cathode system a record high energy density of ∼506 Wh kg–1. The findings highlight new opportunities for the design of high‐energy zinc batteries with both Zn2+ and anions as charge carriers.